2021
DOI: 10.3390/su132011502
|View full text |Cite
|
Sign up to set email alerts
|

PARO as a Biofeedback Medical Device for Mental Health in the COVID-19 Era

Abstract: The COVID-19 pandemic is spreading across the globe, and it could take years for society to fully recover. Personal protective equipment (PPE), various hygiene measures, and social distancing have been implemented to reduce “human to human” contact, which is an essential part of outbreak prevention. The pressure of the pandemic combined with decreased communication and social contact have taken a toll on the mental health of many individuals, especially with respect to anxiety and depression. Effective use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…This study showed that the PARO intervention could effectively reduce the symptoms of depression in depressed older adults with dementia. Our findings corroborate the ideas of Hung et al (2021), who suggested that PARO could be a resource to help support the psychosocial needs of people with dementia in care settings to optimize person-centred care, involving inclusion, identity, attachment, occupation and comfort (Kitwood, 1997). Older adults might alleviate their level of depression by chatting to and stroking PARO to comfort their mood during the interaction.…”
Section: Discussionsupporting
confidence: 86%
“…This study showed that the PARO intervention could effectively reduce the symptoms of depression in depressed older adults with dementia. Our findings corroborate the ideas of Hung et al (2021), who suggested that PARO could be a resource to help support the psychosocial needs of people with dementia in care settings to optimize person-centred care, involving inclusion, identity, attachment, occupation and comfort (Kitwood, 1997). Older adults might alleviate their level of depression by chatting to and stroking PARO to comfort their mood during the interaction.…”
Section: Discussionsupporting
confidence: 86%
“…The growing research interest in anthropomorphism has facilitated marketing studies on how anthropomorphism shapes consumers' judgment and choice, and extensive work explores how anthropomorphizing products affect consumers' responses (Table 1). However, little research examines anthropomorphism in the medical context to define the effect of medical AI's level of anthropomorphism on patients (Bickmore et al, 2010; Shen et al, 2023; Shibata et al, 2021). The rapid development of AI necessitates comparing the effects of highly anthropomorphic medical AI robots with those of human doctors on patients' choices in the medical context.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Current evidence suggests that pet robots can elicit positive impacts on several psychosocial dimensions of people with dementia in long-term care settings, such as reduced agitation, improved mood and social interactions ( 12 14 ). Correspondingly in practice, pet robots continue to be implemented in care settings to support the social health of people with dementia ( 15 ). However, adopting pet robots for dementia care remains a contentious topic, as their ethical underpinnings are still heavily debated ( 16 ).…”
Section: Introductionmentioning
confidence: 99%